PENDIDIKAN KARAKTER CINTA TANAH AIR MELALUI PROGRAM HARMONI HIJAU DI SEKOLAH DASAR NEGERI PERBATASAN SAMBAS - MALAYSIA - Mustapa, Mustapa; Asrori, M.; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to know the character education of love homeland through at green  harmony program at Border State Elementary School Sambas - Malaysia. Which viewed from aspect of planning, implementation, and evaluation of learning characteristic of green harmony. Place of research conducted at 03 Sajingan Besar Elementary School  and 7 Sasak Elementary School. This research is a qualitative research that produces descriptive data. The subject of this research were headmasters, teachers, and students. Data collected by  interview, observation, and documentation. Data were analyzed using data analysis techniques with data collection steps, data reduction, data presentation, and data verification (drawing conclusions). Technique examination of data validity by using technique triangulation and source. The results showed that character education through green schools program implemented in the planning, implementation, and evaluation of  learning is running well. Characteristic learning planning begins with an understanding of school programs and planning of learning scenarios. The implementation of learning is carried out by applying SERU's learning (happy, effective, friendly, unique) and contextual learning approaches. Characteristic learning evaluation is conducted by observation, anacdetal record, and portfolio Keywords: Character education, love homeland,  green harmony